2015
DOI: 10.5154/r.rchscfa.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Encinos mexicanos, un recurso no maderable con potencial para elaborar bebidas tipo Kombucha

Abstract: O aks (Quercus spp.) are some of the world's most important and abundant trees in nearly all temperate forests of the northern hemisphere. There are two diversity centers for this genus: one is in Southeast Asia, and the other is in Mexico. Studies on the use of oak have mainly highlighted its timber applications. However, its non-timber value is still unappreciated. Ethnobotanical tradition shows infusions from Quercus leaves, alone or in combination with other plants, which have anticarcinogenic effects in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Because they are economical, they have become one of the most profitable woods for this industry [ 13 , 21 ]. In Mexico, around 150 species have been reported, representing the second most important forest resource and used mainly for manufacturing handicrafts, firewood, and charcoal [ 74 , 75 ].…”
Section: Oak Extract As a Source Of Natural Antioxidant Additives Aga...mentioning
confidence: 99%
See 3 more Smart Citations
“…Because they are economical, they have become one of the most profitable woods for this industry [ 13 , 21 ]. In Mexico, around 150 species have been reported, representing the second most important forest resource and used mainly for manufacturing handicrafts, firewood, and charcoal [ 74 , 75 ].…”
Section: Oak Extract As a Source Of Natural Antioxidant Additives Aga...mentioning
confidence: 99%
“…Phenolic compounds are the most abundant and have been found to have high antioxidant capacity, with gallic acid, ellagic acid, and ellagitannins identified as potent antioxidant compounds [ 21 ]. In vitro and in vivo studies of oak extracts have demonstrated high antioxidant capacity, with variations in their potency depending on the species, part of the oak used, and external factors such as seasonal changes and level of maturity [ 13 , 43 , 75 , 77 ]. Further research can be conducted to explore the chemical composition of different Quercus species to determine the best oak parts for extraction and to investigate the functional properties and potential health benefits of these extracts when applied in food systems.…”
Section: Oak Extract As a Source Of Natural Antioxidant Additives Aga...mentioning
confidence: 99%
See 2 more Smart Citations
“…Yeasts such as Schizosaccharomyces pombe and Saccharomycodes ludwigii have also been identified [19,20]. Several industrial sectors benefit from SCOBY, such as the food industry, biotechnological processes, and biomedicine [21][22][23].…”
Section: Introductionmentioning
confidence: 99%